Penyuluhan Optimalisasi Manajemen Pemasaran Syariah Dan Potensi Zakat Pada Pabrik Tahu Dan Tempe - Ritonga, Rahmatika; Tiara Putri, Bella; Rambe, Legiman (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2025)
The lack of understanding among Micro, Small, and Medium Enterprises (MSMEs) regarding sharia-based marketing management and the obligation of business zakat remains a major challenge, especially among local food producers such as tofu and tempeh businesses. This community service project aimed to strengthen both managerial and spiritual capacities of entrepreneurs through education and mentoring based on Islamic values in business practices. The method used was Participatory Action Research (PAR), directly involving the owner and employees of Pabrik Tahu dan Tempe Pak Wujud in Rambah Muda, Rokan Hulu. Activities included observation, training, simulation, and continuous evaluation. The results show significant improvements in understanding of sharia marketing, the ability to calculate and distribute business zakat, and more ethical and professional business behavior. The partner began implementing simple financial records, ethical promotions, and fair pricing strategies. In conclusion, the participatory approach proved effective in encouraging sustainable behavioral change and fostering Islamic economic awareness. This model can be replicated to empower other MSMEs based on Islamic economic values.